Diagnosing acute myocardial infarction with troponins: how low can you go?. Issue 4 (12th April 2010) - Body, Richard; McDowell, Garry; Carley, Simon; Ferguson, Jamie; Mackway-Jones, Kevin
Abstract : Background: Recent consensus guidelines state that acute myocardial infarction (AMI) may be diagnosed in the context of a troponin rise above the 99th percentile of the upper reference limit (URL) with the optimal imprecision of the assay (coefficient of variation, CV) being ≤10%. However, at the 99th percentile, modern assays do not have a CV ≤10%. Objective: The authors compared the prognostic implications of placing the diagnostic troponin cut-off at the 99th percentile and at the lowest concentration with a CV ≤10% (functional sensitivity). Methods: The authors prospectively recruited 804 patients presenting to the Emergency Department of a university-affiliated teaching hospital with suspected ACS. All patients underwent 12 h troponin T testing and were followed up by telephone and chart review. Outcomes: Death or AMI (excluding the index event) and the occurrence of major adverse cardiac events (MACEs) within 6 months. Results: Troponin T elevation below the functional sensitivity predicted the risk of death and AMI (adjusted OR 4.6, p=0.039) and MACE (adjusted OR 11.10, p<0.0001) independently of the Thrombolysis in Myocardial Infarction risk score and creatinine levels. Utilising the 99th percentile cut-off, an extra 17 MACEs could be predicted per 1000 patients treated at a cost of identifying 11 patients who would not have developed an event. Conclusions: The results suggest that adopting the lower troponin cut-off would reduce the proportion of 'false negatives' (patients with negative troponin who develop MACE) from 9.6% to 8.9%. Whether this reduction in 'false negatives' justifies the increase in 'false positives' warrants further investigation and discussion.